STUDENTS’ DIFFICULTIES IN PRODUCING SPOKEN LANGUAGE: A CASE STUDY AT ENGLISH DEPARTMENT FKIP MATARAM UNIVERSITY ACADEMIC YEAR 2019/2020 - Sukroini, Yulia; Amrullah, Amrullah; Lail, Husnul (Jurnal Ilmiah Pendidikan Indonesia, 2021)
This research was intended to (1) investigate students’ difficulties in producing spoken language and (2) some factors that contributing to those difficulties. The method used in this research was descriptive qualitative. The subject of this research was 48 students at general speaking from III B morning and III D afternoon class academic year 2018/2019. Methods of data collection used by the researcher were questionnaire and interview. Based on the result of students’ questionnaire showed that 83.3% were lacked of grammar, 87.5% poor on vocabulary and 79.2% often mispronounced the English words. Then, based on the result of questionnaire showed some factors that contributing to their difficulties related to psychological factors, were; lack of motivation and self-confidence, anxiety, shyness and fear of making mistakes. The main factor was shyness. It was indicated by 77.1% of the students faced that problem.